2021
DOI: 10.3897/pharmacia.68.e70452
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis in community pharmacies: a survey on italian pharmacists’ management and implications on corticophobia

Abstract: Community pharmacists represent an important resource for the promotion of a safer and more effective self-management of common skin diseases, as well as the provision of educational support on therapies prescribed by clinicians, ultimately improving patients’ adherence. In this study, a semi-structured survey was administered to 154 Italian community pharmacists, in order to acquire information on their counseling activity on dermatological disorders. Collected data provide an overview on the frequency and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Most studies (n = 19) were conducted in OECD countries: six studies were conducted in the United Kingdom [34][35][36][37][38][39]; two studies were conducted in each of Australia [40,41], Netherlands [42,43], Sweden [44,45], and Japan [46,47]; and one study was conducted in each of Portugal [48], France [49], Germany [50], Belgium [51], and Italy [52]. Moreover, one study was conducted in a GCC (Gulf Cooperation Council) nation, i.e., the United Arab Emirates [53].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies (n = 19) were conducted in OECD countries: six studies were conducted in the United Kingdom [34][35][36][37][38][39]; two studies were conducted in each of Australia [40,41], Netherlands [42,43], Sweden [44,45], and Japan [46,47]; and one study was conducted in each of Portugal [48], France [49], Germany [50], Belgium [51], and Italy [52]. Moreover, one study was conducted in a GCC (Gulf Cooperation Council) nation, i.e., the United Arab Emirates [53].…”
Section: Resultsmentioning
confidence: 99%
“…A majority of studies (n = 20) were published in the period 2011-2021 and reported quantitative findings (n = 18). Of these studies, 14 were cross-sectional studies [37,39,40,[46][47][48][49][50][51][52][53][54][55][56] and 4 were pre-and post-education intervention studies [34,41,43,44]. Three were qualitative research [35,42,45].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations